Screening for endophytic bacteria from Ambon Banana (Musa paradisiaca) as biocontrol agent of anthracnose (Colletotrichum gloeosporioides) on bananas fruit - ARTINI PANGASTUTI; HESTI PRATIWI; RATNA SETYANINGSIH (Nusantara Bioscience, 2023)
Abstract. Pangastuti A, Pratiwi H, Setyaningsih R. 2023. Screening for endophytic bacteria from Ambon Banana (Musa paradisiaca L.) as biocontrol agent of anthracnose (Colletotrichum gloeosporioides) on bananas fruit. Nusantara Bioscience 15: 238-244. Post-harvest Ambon Bananas (Musa paradisiaca L.) are sensitive to anthracnose disease, caused by Colletotrichum gloeosporioides, and causes the fruit to rot quickly. Thus, chemical fungicides are employed, damaging living organisms and the environment. One solution is biocontrol using endophytic microorganisms as antagonistic agents against the anthracnose fungus that causes anthracnose disease. This study aimed to obtain potential endophytic bacteria from the Ambon Banana plant that had inhibitory activity against the growth of the pathogenic fungus C. gloeosporioides that causes anthracnose in bananas. Endophytic bacteria were recovered from Ambon Banana roots by crushing plant components. Therefore, bacterial isolates were tested for antagonistic interactions with pathogenic fungi using the dual culture approach. The 16S rRNA gene sequence analysis was used to identify bacterial isolates with the most significant inhibitory potential. According to the findings of this study, seven isolates of endophytic bacteria, A2-1, A2-2, A5-2, A6-2, A6-3, A8-1, and A9-1, can limit the growth of the pathogenic fungus C. gloeosporioides. The strain A6-3, identified as Pseudomonas pseudoalcaligenes, exhibited the greatest potential as a biocontrol agent against the pathogenic fungus C. gloeosporioides. It achieved the highest inhibition rate of 43.59%, resulting in an extended fruit shelf life and reduced harm susceptibility.